The relationship between physical activity and college students’ sense of security: the chain-mediated role of self-esteem and psychological capital - Hongbo Zhao; Qing You; Lei Shi (Scientific Reports)
Abstract To explore the relationship between physical activity and college students’ sense of security, as well as the mediating role of self-esteem and psychological capital between the two. This study used a cross-sectional design, and questionnaires were distributed to 593 college students (29.7% male and 70.3% female) selected from selected colleges and universities in the Liaoning region of China through a simple random sampling method. The questionnaires included the Physical Activity Scale, the Sense of Security Scale, the Self-Esteem Scale, and the Psychological Capital Scale. Data were analyzed using SPSS 26.0 and PROCESS 3.4 plug-ins and Bootstrap methods to test the chain-mediated effects of self-esteem and psychological capital. (1) there is a positive correlation between physical activity and college students’ sense of security, and the direct prediction of sense of security is significant; (2) physical activity can positively predict self-esteem, self-esteem can positively predict psychological capital and sense of security, and psychological capital can positively predict sense of security; (3) self-esteem and psychological capital play a significant mediating role between physical activity and sense of security, and the three mediating effect paths: physical activity → self-esteem → sense of security, physical activity → psychological capital → sense of security and physical activity → self-esteem → psychological capital → sense of security. (1) Physical activity can significantly and positively predict college students’ sense of security; (2) Self-esteem and psychological capital play mediating roles between physical activity and college students’ sense of security, respectively, and also play chain mediating roles.